2017
DOI: 10.19082/3605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Attachment Styles to Parents on Sexual Dysfunction Domains of Married Women

Abstract: IntroductionAccording to Bowbly attachment theory, attachment of a baby and its main care provider, influences on social growth and the baby’s feelings throughout its life. The present study was performed aim to determine the effect of attachment style to parents on domains of sexual dysfunction in married women.MethodsThis cross-sectional study was carried out on two hundred married women who were fertile, and referred private and governmental gynecology clinics in Mashhad, Iran, in 2014. Data collection tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Several studies demonstrated that there is a positive relationship between unhealthy attachments and narcissism (42,43). Sexual problems in individuals with insecure attachment style were highlighted in many studies as well (44)(45)(46)(47).…”
Section: Insecure Relationshipmentioning
confidence: 99%
“…Several studies demonstrated that there is a positive relationship between unhealthy attachments and narcissism (42,43). Sexual problems in individuals with insecure attachment style were highlighted in many studies as well (44)(45)(46)(47).…”
Section: Insecure Relationshipmentioning
confidence: 99%